The alternatives indicates that the question is aboud even and odd function.
An even function is one the gives:
![f(x)=f(-x)](https://img.qammunity.org/2023/formulas/mathematics/high-school/d5txlwfgs1sgi42dr82a0kuoncotldq3mc.png)
While an odd function is one tha gives:
![f(x)=-f(-x)](https://img.qammunity.org/2023/formulas/mathematics/high-school/b803d0gvcdhyp92p5ivxh6dphoz8vg6qxx.png)
The fisrt function is:
![\begin{gathered} f(x)=\cos ^3(x^3-x) \\ f(-x)=\cos ^3((-x)^3-(-x))=\cos ^3(-x^3+x)=\cos ^{}^(3)(-(x^3-x)) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/lbanjcj19r9b1yztqk3f53olohh0twx4j1.png)
Since
![\cos (x)=\cos (-x)](https://img.qammunity.org/2023/formulas/mathematics/college/vfpc1u9iu6fwa608iibmqrvgszb2qzpybq.png)
Then
![\begin{gathered} \cos ^3(-(x^3-x))=\cos ^3(x^3-x) \\ f(x)=f(-x) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/67cio5007nml0d1tstjyylfa53v08pbl7z.png)
So, f is even.
We can do it similarly for g(x)
![\begin{gathered} g(x)=\ln (|x|+3) \\ g(-x)=\ln (|-x|+3)=\ln (|x|+3) \\ g(x)=g(-x) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/szf50rvqi5rgof2j74h4b4y1flg4xp1uuo.png)
For s(x), we have:
![\begin{gathered} s(x)=\sin ^(3)(x) \\ s(-x)=\sin ^(3)(-x) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/awdyv82p88z6qlvkzx8k0f1nh9ke8vwdzi.png)
Since:
![\sin (-x)=-\sin (x)](https://img.qammunity.org/2023/formulas/mathematics/college/3a7mx5jlsdtwv2yuny7ewwmhxok8k78vkb.png)
Then:
![\begin{gathered} \sin ^3(-x)=(-\sin (x))^3=-\sin ^(3)(x) \\ s(x)=-s(-x) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/j3e45v65ccimsb4mihurrg4521hpmlxsf4.png)
So far we have f(x) even, g(x) even and s(x) odd. This is exactly what is said in alternative A:
A. f and g are even, s is odd.
so that is the right answer.